Quality Management System Admin Module Development: A Study in the Department of Computer Science - Tamara, Anggie; Kurniawan, Didik; Tristiyanto, Tristiyanto; Sakethi, Dwi (International Journal of Electronics and Communications Systems, 2023)
Elevating the quality of learning is central to ensuring academic programs align with national standards. One crucial aspect of this process is the semester-based learning planning. Traditionally, the Department of Computer Science orchestrates this planning by creating separate documents for various data points, including courses, CPL (Graduate Learning Outcomes), and CPMK (Course Learning Outcomes), which are then integrated into the RPS (Semester Learning Plan) document each term. This study seeks a solution to enhance the efficiency of such data management through the development of an admin module. The system, designed using the Rapid Test Development (RAD) approach and the Laravel framework, offers a more effective data management solution, subsequently elevating the pedagogical quality of the Department of Computer Science. In conclusion, an integrated approach to data management can make a significant contribution to educational quality. Through this research, the scholarly contribution provided is the introduction of a systematic model in educational data management to boost the efficiency and effectiveness of the learning process in higher education institutions